2018
DOI: 10.37856/bja.v93i1.3228
|View full text |Cite
|
Sign up to set email alerts
|

HUMIC ACID AND Azospirillum brasilense APPLIED TO COTTON SEEDS

Abstract: Objetivou-se avaliar o efeito da inoculação de Azospirillum brasilense na presença e ausência de substâncias húmicas aplicados em sementes de algodão. Foi aplicada uma dose única de ácido húmico Humykos®: 3 mL kg-1 de sementes; e seis doses do biorregulador Stimulate®: 0; 50,0; 100,0; 150,0; 200,0 e 250,0 mL kg-1 de sementes. Avaliou-se o índice de velocidade de emergência, a percentagem de emergência e de germinação, a contagem de plântulas anormais, o comprimento da parte aérea, da raiz e o comprimento total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
1
0
1
Order By: Relevance
“…The germination of C. leptophylla, L. pacari, M. flocculosa and S. terebinthifolius seeds was not positively affected by the inoculation of A. brasilense, demonstrating that this specific bacterium does not favor the germination process and growth of seedlings of the studied species. The use of rhizobacteria in cotton showed excellent results in seed germination and shoot growth (LIMA et al, 2018), while in wheat there was no significant difference (GALEANO et al, 2019). In forest species, Rampim et al (2014) observed that inoculation in seeds of P. dubium and L. leucocephala with strains of A. brasilense and Bradyrhizobium elkanii significantly increased seedling emergence, allowing a better adaptation of the stand in the production systems employed.…”
Section: Discussionmentioning
confidence: 99%
“…The germination of C. leptophylla, L. pacari, M. flocculosa and S. terebinthifolius seeds was not positively affected by the inoculation of A. brasilense, demonstrating that this specific bacterium does not favor the germination process and growth of seedlings of the studied species. The use of rhizobacteria in cotton showed excellent results in seed germination and shoot growth (LIMA et al, 2018), while in wheat there was no significant difference (GALEANO et al, 2019). In forest species, Rampim et al (2014) observed that inoculation in seeds of P. dubium and L. leucocephala with strains of A. brasilense and Bradyrhizobium elkanii significantly increased seedling emergence, allowing a better adaptation of the stand in the production systems employed.…”
Section: Discussionmentioning
confidence: 99%
“…Nesta mesma linha, porém trabalhando com outra bactéria,Santos et al (2016) afirmaram haver potencial no isolado bacteriano UAGF76, endofítico de raiz, para a promoção de crescimento de plantas, testado em feijão caupi. também observou potencial para promoção de crescimento de plantas quando proporcionou coinoculação com bactérias diazotróficas, obtendo plantas com sistema radicular mais desenvolvido, enquanto no trabalhode Lima et al (2018) o Azospirillum prejudicou o comprimento da parte aérea.Para massa seca de parte aérea e radícula obtidos a partir do teste de crescimento de plântulas também não houve diferença (Tabela 2), confirmando os resultados para a massa seca de parte aérea deBulegon et al (2014), que não encontraram diferenças significativas para as cultivares avaliadas, mas observaram diferença em massa seca do sistema radicular, tanto entre as cultivares testadas quanto entre tratamentos com inoculação. Entretanto,Libório et al (2016) demonstraram resultados contrários, em que a massa seca de parte área apresentou significância estatística, com superioridade da coinoculação (Bradyrhizobium + Azospirillum) e não diferença significativa para massa seca de sistema radicular e para sementes de algodão, enquanto Lima et al…”
unclassified